Enhanced functionality of miRNA-encapsulated chitosan nanoparticles as an anti-migration agent for cancer therapy - Yahya Ariff, Syazaira Arham (2017)
Despite advanced treatments in cancer therapy, there are still high incidences and mortality rates for cancer globally with expectations of 23.6 million new cancer cases by 2030. An inherent drawback towards the success of current treatment is the increases metastasis of the primary tumours to other body parts in advanced stage cancers. Current therapeutics therefore could potentially target metastasis routes as a means for novel cancer treatment strategies. Recently, microRNAs (miRNA) have been utilized as a repressor molecule for metastasis, as it inhibits fundamental processes related to cellular and physiological pathway of the tumour at the mRNA level. However, therapeutic applications of miRNAs is impaired by premature degradation in the extracellular environment by endonucleases. Nanoparticles can therefore be used as delivery vehicles for miRNA to increase its cellular uptake, as they confer protection to the miRNA from extracellular enzymatic degradation. The aim of this study was to develop optimal parameters for the synthesis of chitosan nanoparticles (CNP) using chitosan (CS) and sodium tripolyphosphate (TPP), a drug carrier with high particle stability, low cellular toxicity, and robust preparation methods through ionic gelation method for effective encapsulation of plasmid precursor miRNA186 (ppmiR186). A CNP nanoparticle system was subsequently developed and characterized physico-chemically, followed by an evaluative assessment of the efficiency for synthesized ppmiRNA186-encapsulated chitosan nanoparticle (CNP-ppmiR186) system to decrease the metastasis of cancer cells in vitro. Physico-chemical analyses using TNBS assay showed a decrease in free amine group of CS with increasing TPP volume, an indicator for utilization of protonated amine groups in CS by anionic phosphate groups of TPP to form CNP. Subsequent Dynamic Light Scattering (DLS) analysis of the nanoparticles showed a 135% increased of particle size from 84.06 nm to 197.63 nm and PDI from 0.28 to 0.37 after incorporation of 100 μg/μl ppmiR186; an encapsulation efficiency of 48% to form CNP-ppmiR186. Through gel electrophoresis, encapsulation of ppmiR186 in CNP showed that CNP-ppmiR186 formed a neutrally charged moiety, as no band was separated compared to naked ppmiR186. Further morphological analysis using FESEM and TEM showed a spherical shape for both CNP and CNP-ppmiR186 and correlated accordingly to particle sizes measured through DLS. Additionally, important functional groups (amine, inorganic and organic phosphate) in each molecule of CS, TPP, ppmiR186, CNP and CNP-ppmiR186 were observed in the corresponding CNP-ppmiR186 nanoparticle system. The nanoparticle system was then treated to A549 lung cancer cells, and evaluated the efficacy of ppmiR186. The resulted CNP-ppmiR186 was delivered in A549 cells of non-small cell lung carcinoma (NSCLC) expressed the miRNA-186 gene cassette, as shown by the sequential expression of an upstream green fluorescent protein (GFP) gene in transfected cells. Cell scratch and cytotoxicity assays were then conducted to determine metastasis and proliferation abilities of cancer cells after treatment with the nanoparticles. Both CNP and CNP-ppmiR186 successfully hindered migration of A549 cells in cell scratch assays, as the scratch gap on the monolayer cell only decreased by 1% and 4%, respectively compared to non-treatment groups. Finally, anti-proliferative effect of the CNP-ppmiR186 determined through MTT assay showed a 59% cell viability in cells treated. Moreover, CNP was ascertained as a safe delivery vehicle, as 68% cell viability was achieved even at its highest concentration of treatment. In conclusion, based on physiochemical analysis and cellular treatments, ppmiR186 was successfully encapsulated in CNP and the resulting CNP-ppmiR186 is suggested to possess enhanced anti-metastatic and anti-proliferative effect on A549 cells of NSCLC compared to naked delivery of ppmiR186. This system thus has the potential to be further developed as a novel cancer therapy preventing metastasis in cancers, and towards future aversion of cancer progression in patients.